2016
DOI: 10.1155/2016/9235073
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Liver Transplantation Outcome by Heme Oxygenase‐1‐Transduced Bone Marrow Mesenchymal Stem Cells in Rats

Abstract: Bone marrow mesenchymal stem cells (BMMSCs) exert immunosuppressive activity in transplantation, and heme oxygenase-1 (HO-1) enhances their immunomodulatory effects. The aim of this study was to determine whether HO-1-transduced BMMSCs (HO-1/MSCs) improve rat liver transplantation (LTx) outcomes. Orthotopic LTx rejection models were treated with HO-1/MSCs, BMMSCs, HO-1, or normal saline, respectively. Our results showed a significant improvement in survival rates in the HO-1/BMMSCs group compared to the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 30 publications
(28 reference statements)
5
43
0
Order By: Relevance
“…After cutting off both ends of the epiphyseal, the marrow cavity was rinsed by DMEM/F12 (Gibco, Thermo Fisher Scientific, Inc., Waltham, MA, USA) containing 10% fetal bovine serum (FBS). Red blood cells were lysed using 0.1 mol/l NH 4 Cl, and the remaining cells were washed, resuspended, and cultured 1×10 6 /T75 culture flask at 37°C with 5% CO 2 in Dulbecco's modified Eagle's medium (DMEM)/F12 containing 100 U/ml penicillin, 100 mg/ml streptomycin and 15% FBS ( 13 ). The well-grown third-passage BM-MSCs were resuspended at 1×10 6 /ml and then labeled with antibodies against CD29 (1:80, PE, 102207), CD90 (1:200, FITC, 202503), CD45 (1:80, PE, 202207), RT1A (1:80, PE, 205208), RT1B (1:200, FITC, 205305) (both from BioLegend, Inc., San Diego, CA, USA) and CD34 (1:5, FITC, sc-7324; Santa Cruz Biotechnology, Inc., Dallas, TX, USA) for 30 min for flow cytometric analysis (BD FACSAria III; BD Biosciences, Franklin Lakes, NJ, USA) of the expression of cell surface markers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After cutting off both ends of the epiphyseal, the marrow cavity was rinsed by DMEM/F12 (Gibco, Thermo Fisher Scientific, Inc., Waltham, MA, USA) containing 10% fetal bovine serum (FBS). Red blood cells were lysed using 0.1 mol/l NH 4 Cl, and the remaining cells were washed, resuspended, and cultured 1×10 6 /T75 culture flask at 37°C with 5% CO 2 in Dulbecco's modified Eagle's medium (DMEM)/F12 containing 100 U/ml penicillin, 100 mg/ml streptomycin and 15% FBS ( 13 ). The well-grown third-passage BM-MSCs were resuspended at 1×10 6 /ml and then labeled with antibodies against CD29 (1:80, PE, 102207), CD90 (1:200, FITC, 202503), CD45 (1:80, PE, 202207), RT1A (1:80, PE, 205208), RT1B (1:200, FITC, 205305) (both from BioLegend, Inc., San Diego, CA, USA) and CD34 (1:5, FITC, sc-7324; Santa Cruz Biotechnology, Inc., Dallas, TX, USA) for 30 min for flow cytometric analysis (BD FACSAria III; BD Biosciences, Franklin Lakes, NJ, USA) of the expression of cell surface markers.…”
Section: Methodsmentioning
confidence: 99%
“…HO-1 can increase the activity and prolong the duration of BM-MSCs ( 11 ). Previous studies of the authors have demonstrated that HO-1-transduced BM-MSCs (HO-1/BM-MSCs) may protect the transplanted liver by participating in the regulation of transplantation immunity and repair of the damaged liver tissue ( 12 , 13 ). However, the mechanism of this protective effect remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with both HO‐1 and MSCs relieved inflammation, while which HO‐MSCs showed the most significant effects (Zeng et al, ). HO‐MSCs may therefore reduce intestinal epithelial injury by inhibiting the release of inflammatory cytokines such as IL‐2, IL‐6, and IFN‐γ, and promoting the release of anti‐inflammatory cytokine IL‐10 (Wu et al, ), leading to increased expression of tight junction proteins and proliferation of intestinal epithelium (Zhang et al, ). HO‐MSCs regulated the expression of cytokines in Caco2 cells, which might be related to the enhanced transforming ability and antioxidant effects of MSCs after Ad‐HO transduction (Vanella et al, ; Zeng et al, ; Hamedi‐Asl et al, ; Vanella et al, ), and both the activity and duration of action were enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Foxp3-overexpressing MSCs generated a state of Treg-dependent tolerance and induced donor-specific allograft tolerance in a contact-dependent mechanism [105]. Transplantation of heme oxygenase (HO)-1-overexpressing MSCs significantly decreased the rejection rate while increasing the survival time of LT rats by increasing the levels of peripheral Tregs and decreasing the levels of NK cells in liver tissue [106,107]. Furthermore, overexpression of HO-1 or IL-10 in MSCs significantly increased the levels of anti-inflammatory cytokines (IL-10 and TGF-β) and decreased the levels of proinflammatory cytokines (IL-2, IL-6, IL-17, IL-23, TNF-α, and IFN-γ) in LT recipients [106][107][108].…”
Section: Immunoregulation Of Mscs In Recipients Who Have Undergone Ltmentioning
confidence: 99%